Peningkatan Kinerja Guru Melalui Supervisi Edukatif Kolaboratif Secara Periodik dalam Kegiatan Pembelajaran Semester II TP 2021/2022 di SMK Negeri 1 Peusangan - Joko Triyanto; Amiruddin; Teuku Salfiyadi (LP. Ma'arif Janggan Magetan, 2022)
This study aims to describe Teacher Performance Improvement Through Periodic Collaborative Educational Supervision in Learning Activities in Semester II TP 2021/2022 at SMK Negeri 1 Peusangan, and as a teaching profession for credit scores (position increases). The approach used in this research is qualitative with the type of school action research (PTS). The results showed that almost all of the 6 teachers were able to carry out learning well. This is evident from the results of supervision. The steps taken to improve the implementation of learning based on this action research are: (1) Researchers who observe teachers teaching not as assessors but as co-workers, (2) During the supervision in the classroom the teacher does not consider the researcher as an assessor, (3) Researchers record all events that occur in learning both positive and negative, (4) Researchers always give examples of learning oriented to Modern Learning. (5) Researchers provide examples of how to explain objectives, present, provide feedback to teachers, (6) Researchers every two or three weeks visit or follow the teacher in the learning process.